Evaluasi Sistem Informasi Akuntansi Penerimaan Pembayaran SPP Sebagai Alat Pengendalian Internal Penerimaan Kas Pada SMA Katolik St. Albertus Malang - Trivena Tabita; Galuh Budi Astuti (Universitas Katolik Widya Karya Malang, 2022)
This study aims to evaluate the accounting information system for receiving tuition fees as an internal control tool for cash receipts at St. Catholic High School. Albertus Malang. This research is a case study research. The data used are qualitative and quantitative data. Primary data sources and secondary data are obtained from research reports, documents, and other supporting data sources. The problem that occurs is that the internal control of cash receipts from payment of tuition fees is still weak. This is due to the absence of an application document for the relief of SPP fines for depositors who are late in making SPP payments and are unable to pay the nominal SPP fines collected. The results of a qualitative descriptive analysis are by adding documents in the form of an application letter for the relief of SPP fines and improving the systems and procedures for cash receipts for SPP fines. This can optimize internal control to run effectively.